The impact of positive psychological intervention on college students' mental health and behavioral performance: the moderating role of teacher empathic concern - Wang, Hui; Xi, Lei (Frontiers in Psychology, 2025)
IntroductionCollege students‘ mental health and behavioral performance have been a hot topic of concern among scholars. With the heavy academic pressure, high social expectations, and uncertainty about future career development, college students' anxiety and depression aspects have become more and more prominent. However, the relationship between positive heart interventions (subjective wellbeing and physical exercise), teachers‘ empathetic attention, college students' mental health and behavioral performance, and their mechanisms still need to be further studied.MethodsThis study aimed to investigate the relationship between positive mindfulness interventions and college students' mental health and behavioral performance, and to verify the moderating role of teachers' empathetic attention between the two. In addition, this study examined the current status of positive mindfulness interventions, teachers' empathic concern, mental health and behavioral performance of 260 Chinese university students by means of a questionnaire survey.ResultsThe results of the study showed that positive heart interventions, subjective wellbeing, and physical activity had a significant role in promoting college students' mental health and behavioral performance, positive heart interventions (β = 0.488, P < 0.001), (β = 0.474, P < 0.001) subjective wellbeing (β = 0.327, P < 0.001), (β = 0.362, P < 0.001), and physical activity (β = 0.254, P < 0.001), (β = 0.203, P < 0.001). In addition, teachers' empathetic attention played a positive moderating role between positive heart interventions and college students' mental health (β = 0.332, P < 0.001). Teachers' empathic concern played a positive moderating role between positive heart intervention and college students' behavioral performance (β = 0.223, P < 0.001).ConclusionThis study provides valuable suggestions for teachers, doctors, and parents to better safeguard the state of mental health of college students and to regulate the behavioral performance of college students to be consistent with the ideal goals they pursue.